Evaluasi Tingkat Kapabilitas Sumber Daya Teknologi Informasi Menggunakan Framework COBIT 5 pada Subdomain EDM04, APO07 dan DSS03 (Studi Kasus : Daerah Operasi XX) - Farah Amalia; Suprapto Suprapto; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
PT Kereta Api Indonesia which provide train transportation in Indonesia has nine areas of operation, one of them is Daerah Operasi XX. PT KAI has vision and mission focusing on customer service. In service operation PT KAI have been using information technology. To create a successful information technology, the role of human resource is necessary. However practically, based on result of an interview, there are problems related to information technology resources, including less than optimal human resource planning and mapping, and also less than optimal service management for customer. It is necessary to evaluate the level capability IT resource using framework COBIT 5 to find out the value of capability level on subdomain EDM04 (Ensure Resource Optimization), APO07 (Manage Human Resource) and DSS03 (Manage Problems). The value of capability level in this research is obtained from several methods, say questioner, interviews, and observation. The results of this evaluation are to get the value of capability level for each subdomain were level 2 while targeted level for each subdomain were 3 with GAP value 1. Recommendation that given for the third subdomain is to focus on planning and mapping of human resource and infrastructure management.